Rectifying analogy-based ınstruction to enhance ımmediate and postponed science achievement - Al-hınaı, Maymoona; Al-balushı, Sulaiman (Journal of Turkish Science Education, 2015)
The aim of this study was to examine the impact of analogy-based instruction on immediate and postponed science achievement. More specifically, the focus of the current study was on the retention of students at three cognitive levels: knowledge, comprehension and application. Two classes of 63 ninth grade female students in Oman participated in the study. These classes were randomly assigned to an experimental group (N=32) which used analogy-based instruction and a control group (N=31) which used the traditional method. An achievement test was designed at the three cognitive levels and was administered to both groups immediately after the conclusion of the study which lasted for five weeks and once again two weeks later. In the immediate administration of the test, the findings indicated that the experimental group significantly outperformed the control group in terms of two cognitive levels, comprehension and application, and also in the overall score of the test. In the postponed test, the experimental group outperformed the control group in all three levels and in the overall score. Also, there was a substantial decline in control group students’ scores in the three cognitive levels and in the overall test score. This was not the case for the students in the experimental group. We have listed several justifications for these findings, recommendations for science teachers and textbook writers, limitations of the study and ideas for further research in the section headed “Conclusions and recommendations” below.